2012
DOI: 10.1001/dmp.2012.69
|View full text |Cite
|
Sign up to set email alerts
|

Incidences, Types, and Influencing Factors of Snow Disaster–Associated Injuries in Ningbo, China, 2008

Abstract: ABSTRACTObjective: The incidence, types, and influencing factors of injuries due to snow-ice disasters are essential for public health preparedness. This study was designed to assess such factors of injuries during the 22-day snowstorm in Ningbo, Zhejiang Province, China, in 2008.Methods: A multistage cluster probability sampling method was applied to select the study population in urban, rural, and mountainous area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…Two studies investigated the following risk factors for being injured during an extreme event: age above 45 years, female sex [ 31 , 32 ], being outdoors, destruction of the house, tin construction materials [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies investigated the following risk factors for being injured during an extreme event: age above 45 years, female sex [ 31 , 32 ], being outdoors, destruction of the house, tin construction materials [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Over the past decade, the intensity and frequency of natural and man-made disasters have been noticeably increasing all over the world. Hurricane, earthquake, flood, outbreaks of infectious diseases, nuclear leakage, oil spills, and other disasters in recent years have caused huge economic losses, serious environmental disruption and lasting psychological impairment to the survivors [1][2][3][4][5]. Community residents are the very ones directly affected by disasters.…”
Section: Introductionmentioning
confidence: 99%
“…Outdoor activities of the elderly in extreme temperature would signi cantly reduce (Collins et al, 1977), thereby reducing the possibility of exposure to fall risk factors, which is a reason for the reduction of FRIs in the elderly in high temperature. Studies have shown that FRI in the elderly in winter is related to walking on wet and slippery roads (Xu et al, 2012). Low temperature caused lower body temperature, decreased exibility, slower reaction speed, changes in physiological processes (Keatinge et al, 1984;Riley and Cochran, 1984), and wearing heavy clothes, all of which would increase the risk of falls for elder (Lin et al, 2015).…”
Section: Discussionmentioning
confidence: 99%